La crisis del sistema transnacional y el cambio en las relaciones internacionales de los países en desarrollo - Sunkel, Osvaldo; Tomassini, Luciano (Estudios Internacionales, 1980)
This work supports that the terms in which center-periphery relations were traditionally considered have changed significantly over the last two decades, as a result of the progress of the transnationalization process that has taken place on a global scale, giving rise to a relationship of interdependence at the world level. It is also argued that the crisis of the contemporary transnational system has accentuated this relationship of interdependence and that, to a certain extent, interdependence is not only a reality between industrialized countries but also between them and developing countries, even if it is a " interdependence between unequals ". Therefore, the pace and style of development of the peripheral countries will be increasingly associated with the degree and form it takes them to integrate into the transnational system.